2013
DOI: 10.4187/respcare.02549
|View full text |Cite
|
Sign up to set email alerts
|

ChronicPseudomonas aeruginosaInfection and Respiratory Muscle Impairment in Cystic Fibrosis

Abstract: BACKGROUND: Chronic infection with Pseudomonas aeruginosa in patients with cystic fibrosis (CF) is associated with increased morbidity. Chronic infection can cause limb and respiratory muscle compromise. Respiratory muscle function can be assessed via maximal inspiratory pressure (P Imax ), maximal expiratory pressure (P Emax ), and the pressure-time index of the respiratory muscles (PTI mus ). We studied the effect of chronic P. aeruginosa infection on respiratory muscle function in patients with CF. METHODS:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
2
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 41 publications
1
24
2
5
Order By: Relevance
“…Importantly, an animal study showed that CF mice with sustained infection with P. aeruginosa had a reduced diaphragmatic force-generating capacity [9]. Furthermore, a detailed study on the impact of P. aeruginosa infection on respiratory mechanics in adolescent CF patients clearly showed that P. aeruginosa infection can indeed have an independent effect on respiratory muscle function [7]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, an animal study showed that CF mice with sustained infection with P. aeruginosa had a reduced diaphragmatic force-generating capacity [9]. Furthermore, a detailed study on the impact of P. aeruginosa infection on respiratory mechanics in adolescent CF patients clearly showed that P. aeruginosa infection can indeed have an independent effect on respiratory muscle function [7]. …”
Section: Introductionmentioning
confidence: 99%
“…Despite the link between P. aeruginosa infection and respiratory disturbances, respiratory mechanics are rarely investigated in CF patients. In general, the load imposed on the respiratory muscles, respiratory muscle efficiency, and respiratory muscle strength are all key factors in determining respiratory mechanics [7]. In particular, the impact of P. aeruginosa infection on respiratory mechanics is not fully understood, but it is suggested to be clinically important, since chronic infection has been shown to impair respiratory muscle function [8].…”
Section: Introductionmentioning
confidence: 99%
“…13 Once infection is established, there is an accelerated decline in lung function, quality of life, and survival. 14,15 Furthermore, chronic P. aeruginosa infection has been related to decreased maximum inspiratory pressure (P Imax ) and is probably an independent predictor of respiratory muscle compromise in cystic fibrosis, 16 although its relation to muscle endurance remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…13 On their side, Gollee et al observed that superficial abdominal muscle functional stimulation increased PCF and tidal volume in tetraplegic subjects. 21 The linear regression analysis done in our study estimated that per every cmH 2 each other. In biomechanical terms, during cough mechanism, expiratory muscles play a critical role both during relaxation in the inspiratory phase and during isometric contraction in the compression phase, which allows raising intraabdominal pressure up to 300 mmHg.…”
Section: Discussionmentioning
confidence: 99%